Edward Rondthaler. - (:unkn) unknown (Forsyth County Public Library, 2010)
Source: "Biographical History of North Carolina; From Colonial Times to the Present." 1905.
Edward Rondthaler.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth